A case report of systemic lupus erythematosus combined with central serous chorioretinopathy treated with glucocorticoids. Issue 3 (March 2023) - Rao, Qingqing; Ku, Ming; Wan, Qijun
Glucocorticoids are generally contraindicated for use in central serous chorioretinopathy (CSC) because their use is considered to be an independent risk factor for CSC. There are rare reports regarding the treatment of systemic lupus erythematosus (SLE) combined with CSC. This current case report describes a rare case of a 24-year-old female patient with severely active SLE combined with CSC, whose vision was significantly restored after she was administered 120 mg methylprednisolone intravenously once a day for 3 days. This case report presents the clinical characteristics for the first time in terms of distinguishing between typical CSC and lupus chorioretinopathy. It also provides a review of the relevant literature. In patients with clinically severe active lupus nephritis combined with bilateral lupus chorioretinopathy, timely systemic application of appropriate doses of glucocorticoids is the preferred method to control the primary disease and serious ocular complications.